Building stories -- the art of the project manager in exhibition development : an analysis of Death and Diversity at Wellington Museum : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Museum Studies, at Massey University, Manawatū, New Zealand - Fafeita, Brent Raymond (Massey University, 2016)
This thesis examines the role of both project management and the project manager in museum exhibition development at one museum. Specifically it investigates the necessity of such practice and the various inherent factors that lead to exhibition development success. It argues that project management is not only vital to this success but that such success is dependent on the unique skill and ability of the project manager. Ultimately this thesis advocates for a special breed of project manager suited to the museum environment. Owing to limited museum-based research in this field, it is unclear how effective project management is in developing museum exhibitions and subsequently, understanding the effectiveness of the project manager’s contributions to this process. This research provides a much-needed qualitative study that not only examines the role, but also provides insight into the mindset of one such professional. In addition to introducing museum project management, an in-depth case study focusing on the Wellington Museum (former Museum of Wellington City & Sea) investigates the intricacies associated with this practice. In particular it centres on the Death and Diversity exhibition staged in 2011, where the Museum initiated an inaugural project manager role and then retained it for a large-scale capital development planned for completion in 2020. Utilising qualitative research methods this thesis builds three sections: a context chapter, one case study, and an ethnographic study. Open-ended, in-depth interviewing of both the Museum’s project manager and the director give valuable insight into the practice and perceptions about the role. An observational study examines project manager behaviour and interaction during project meetings. The analysis highlights the complexities of contemporary exhibition development. In an increasingly evolving and resource-limited world of equally increasing scrutiny, this advocates for a profession tailor-made for such complexity in the unique museum environment.
Keywords: Museum exhibits; Design; Project managers; Wellington Museum; Wellington; New Zealand; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects